Lobektomi Life Saving pada Hemoptisis Berulang pada Tuberkulosis Paru : [Hemoptysis in Aspergiloma Patient: A Case Report] - Soedarsono Soedarsono; Tri Puji Astuti (Jurnal Respirasi, 2019)
Background. Hemoptysis is the most common complication of lung tuberculosis (TB). Its can occur repeated and massive. Reccurent massive hemoptysis resolved with conservative therapy but if conservative therapy fails, definitive therapies such as lobectomy surgery are used as alternative treatments especially life-threatening. Case. A 38-year-old man with chief complaint hemoptysis since 4 months pior to admission hospital. Hemoptysis 4-5 times daily with volume 200-600 cc per day and make him shortness of breath and anemia. Initial AFB (Acid Fast Bacilli) was positive and GeneXpert MTB (+) sensitive rifampisin. He got Anti Tuberculosis Drug (ATD) therapy 1st category since 3 months ago. He has been given conservative therapy for hemoptysis but failed. Discussion. Surgery is one of alternative therapy for reccurent massive hemoptysis. Surgery only if source of bleeding already known certainty. In this case patient were suggest for lobectomy superior right lung lobe, not a segmentectomy because there was adhesions on intrathoracic. After lobectomy he getting better and hemoptysis stops. He has continued ATD until 6 months without hemoptysis. Conclusion. Reccurent massive hemoptysis and life-threatening with failure of conservative therapy may given definitive therapy such as lobectomy.